A Conserved Role for LRRK2 and Roco Proteins in the Regulation of Mitochondrial Activity - Rosenbusch, Katharina E.; Oun, Asmaa; Sanislav, Oana; Lay, Sui T.; Keizer-Gunnink, Ineke; Annesley, Sarah J.; Fisher, Paul R.; Dolga, Amalia M.; Kortholt, Arjan (Frontiers in Cell and Developmental Biology, 2021)
Parkinson’s Disease (PD) is the second most common neurodegenerative disease world-wide. Mutations in the multidomain protein Leucine Rich Repeat Kinase 2 (LRRK2) are the most frequent cause of hereditary PD. Furthermore, recent data suggest that independent of mutations, increased kinase activity of LRRK2 plays an essential role in PD pathogenesis. Isolated mitochondria of tissue samples from PD patients carrying LRRK2 mutations display a significant impairment of mitochondrial function. However, due to the complexity of the mitochondrial signalling network, the role of LRRK2 in mitochondrial metabolism is still not well understood. Previously we have shown that D.discoideum Roco4 is a suitable model to study the activation mechanism of LRRK2 in vivo. To get more insight in the LRRK2 pathways regulating mitochondrial activity we here used this Roco4 model system in combination with murine RAW macrophages. Here we show that both Dicyostelium roco4 knockout and cells expressing PD-mutants show behavioural and developmental phenotypes that are characteristic for mitochondrial impairment. Mitochondrial activity measured by Seahorse technology revealed that the basal respiration of D.discoideum roco4- cells is significantly increased compared to the WT strain, while the basal and maximal respiration values of cells overexpressing Roco4 are reduced compared to the WT strain. Consistently, LRRK2 KO RAW 264.7 cells exhibit higher maximal mitochondrial respiration activity compared to the LRRK2 parental RAW264.7 cells. Measurement on isolated mitochondria from LRRK2 KO and parental RAW 264.7 cells revealed no difference in activity compared to the parental cells. Furthermore, neither D.discoideum roco4- nor LRRK2 KO RAW 264.7 showed a difference in either the number or the morphology of mitochondria compared to their respective parental strains. This suggest that the observed effects on the mitochondrial respiratory in cells is indirect and that LRRK2/Roco proteins most likely requires other cytosolic cofactors to elicit mitochondrial effects.